Development of successive karstic systems within the Baix Penedès Fault zone (onshore of the Valencia Trough, NW Mediterranean). Issue 1 (24th June 2013) - Baqués, V.; Travé, A.; Cantarero, I.
Abstract The Baix Penedès Fault zone records successive karstic systems. The outcrops studied correspond to different segments of the fault, which were temporarily connected and disconnected, allowing for different diagenetic processes to occur. The first karstic system affected the Mesozoic rocks due to subaerial exposure after Paleogene compression, an event characterized by widespread dissolution and the generation of vug and cavern porosity. The δ18O values of the dolomitic sediment filling the initial vuggy porosity are similar to those of the host dolomite, indicating that the sediment comes from the erosion and reworking of the host rock. The second karstic system is related to the upward propagation of the Baix Penedès Fault. This deformation was characterized by random‐fracture fabrics with dolomite cement and sediment. The stable isotopes values and Sr/Ca ratios of both the dolomite cement and sediments are similar to those of the host rock. In contrast, the more depleted δ13C values indicate the influence of soil‐derived CO2 and the opening of the system to meteoric waters. During the third karstic event, the δ18O, δ13C, Sr/Ca ratios, and 87Sr/86Sr values of diagenetic cements suggest a marine signature, indicating that the karstic sediments were dolomitized under the influence of late Burdigalian‐Langhian marine waters. These marine waters were probably expelled from poorly buried sediments and circulated through faults producing dolomitization of the karstic sediments. A final karst system developed during a period of uplift and subaerial exposure. The δ18O values, the Mg/Ca and Sr/Ca ratios, and the high radiogenic values of the calcite cements formed during this period indicate precipitation from meteoric waters. The results of this study have implications for carbonate hydrocarbon reservoir analogs subject to karstic influence in the Valencia Trough and elsewhere.